The Respiratory Tract Effectiveness of Post-General Anesthesia in Smokers and Non-Smokers in Pku Muhammadiyah Operating Theaters of Bantul Yogyakarta - Setiawan, Arif Adi; Tanugita, Gusti Agung Putu Anggit Ciwi (Jurnal Keperawatan Respati Yogyakarta, 2020)
The respiratory tract effectiveness of post-general anaesthesia inhalation is greatly influenced by the condition of the respiratory system. The smoking habit causes inflammation of the respiratory tract especially on patients who have smoking record. They have a high risk of respiratory tract ineffectiveness of anaesthesia inhalation. This study aims to compare the effectiveness respiratory tract of post-general anaesthesia inhalation in smokers and nonsmokers in the PKU Muhammadiyah Hospital Operating Theater Bantul Yogyakarta. This study was categorized as a comparative study with a cohort approach involving 36 respondents who were taken by accidental sampling. The results this study was analyzed by Mann-Whitney analysis in purpose to explain that there were differences between smokers respiratory tract effectiveness and nonsmokers post- general anaesthesia inhalation in PKU Muhammadiyah Hospital Operating theatre in Bantul Yogyakarta with a significant value of 0,000 (p <0.05).